2005
DOI: 10.1111/j.0105-2896.2005.00298.x
|View full text |Cite
|
Sign up to set email alerts
|

Conformational isomers of a peptide–class II major histocompatibility complex

Abstract: The relative plasticity of peptide binding to class II major histocompatibility complex (MHC) molecules permits formation of multiple conformational isomers by the same peptide and MHC molecule; such conformers are specifically recognized by distinct subsets of T cells. Here, we review current knowledge and recent advances in our understanding of peptide-class II MHC conformational isomerism and the mechanisms that generate distinct MHC-peptide conformers. We focus on our studies of two T-cell subsets, type A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(45 citation statements)
references
References 121 publications
(193 reference statements)
3
42
0
Order By: Relevance
“…HEL is not glycosylated and is presumably taken up by macropinocytosis when offered in soluble form; HEL can bind to constituents of plasma membranes, such as phospholipids (35) and glycosaminoglycans (36), but receptor-mediated uptake has not been shown. Our data indicate that soluble HEL rapidly enters late endosomes and does not remain in early endosomes for enough time to allow processing and cross-presentation; this feature of soluble HEL trafficking also hindered MHC class II presentation of type B epitopes, which are generated exclusively in early endosomes lacking the accessory molecule DM (37).…”
Section: Discussionmentioning
confidence: 84%
“…HEL is not glycosylated and is presumably taken up by macropinocytosis when offered in soluble form; HEL can bind to constituents of plasma membranes, such as phospholipids (35) and glycosaminoglycans (36), but receptor-mediated uptake has not been shown. Our data indicate that soluble HEL rapidly enters late endosomes and does not remain in early endosomes for enough time to allow processing and cross-presentation; this feature of soluble HEL trafficking also hindered MHC class II presentation of type B epitopes, which are generated exclusively in early endosomes lacking the accessory molecule DM (37).…”
Section: Discussionmentioning
confidence: 84%
“…Antigen loading onto MHC class II molecules can occur in both endosomal recycling compartments and late endosomes and/or lysosomes, and the site of antigen loading can affect the conformer of peptide-MHC class II complex that is displayed at the cell surface. [44][45][46][47] In addition, antibody binding to antigen has been shown in other studies to "protect" epitopes from presentation by MHC class II proteins. [48][49][50][51] Antibodies that bind with pH independence are therefore expected to have two effects on MHC class II-mediated presentation: first, they will recycle antigen away from degradative compartments through FcRnmediated bridging.…”
Section: Supplemental Materialsmentioning
confidence: 96%
“…Consequently, these differences are expected to result in variations in the epitopes that are presented, at both the level of the peptide sequence and the conformer of peptide-MHC complex that is formed. 45 Although here we only consider the targeting of single epitope antigens with monoclonal antibodies, polyclonal mixes of antibodies that form multimeric immune complexes are expected to deliver antigens to late endosomes and/or lysosomes in antigen presenting cells independently of their pH dependence for antigen binding. 54,55 In summary, subcellular trafficking analyses of antigen in the presence of antibodies with a range of pH dependencies can be used to inform the dynamic behavior of targeted antigen within cells.…”
Section: Supplemental Materialsmentioning
confidence: 99%
“…Identification of SDS-stable versus unstable peptide-class II complexes suggested that class II molecules could exist in at least two different conformational states, in this case driven primarily by the properties of the bound peptide (2,3). Identification of "Type A" and "Type B" T cells further suggests the existence of distinct forms of peptide-class II complexes, the formation of which is highly dependent on the mechanism of MHC class II peptide loading (4). Most recently, we identified a subset of signalingcompetent lipid raft-tropic I-A k class II molecules bearing the Ia.2 epitope, which is recognized by the 11-5.2 anti-Ia.2 mAb.…”
Section: Major Histocompatibility Complex (Mhc) Class II Molecules Exmentioning
confidence: 99%